The performance of Islamic and conventional unit trust funds in Malaysia - Ahmad, Maslina; Haron, Razali (2006)
This research reports on the findings of a study that examined the performance of Islamic unit trust funds in comparison with the conventional trust funds in Malaysia. The objectives of the study were to compare the nature and characteristics of both funds, assess their risks and returns profiles, measure the degree of diversification and compare the consistency of performance ranking. The performance of both funds was analyzed over a period of 36 months commencing from February 2000 to January 2003 and evaluated based on the standard performance measures for funds known as Adjusted Sharpe, Treynor and Adjusted Jensen Alpha Indices. The composite index of the Kuala Lumpur Stock Exchange (KLSE) represented the market benchmark for the conventional funds while the Islamic funds used Syariah index as proxy for the market. The findings revealed that on average, the Islamic funds failed to outperform the performance of conventional fund. However, the Islamic funds seemed to have lower risks than the conventional funds. Even so, the independent sample t-test results showed that there was no significant difference in the means performance of both funds.